Zhodnocení finanční situace podniku a návrhy na její zlepšení - Flégl, Martin (Vysoké učení technické v Brně. Fakulta podnikatelská, 2025)
Tato bakalářská práce je zaměřena na zhodnocení finančního stavu společnosti JUTA a.s. a na vytvoření návrhů na jeho zlepšení. Cíle bude dosaženo provedením finanční analýzy za období let 2014–2023. Práce je rozdělena do tří hlavních částí. První část představuje teoretické pozadí vycházející z odborné literatury. Ve druhé části jsou teoretické poznatky aplikovány při finanční analýze vybrané společnosti. Třetí část se věnuje návrhům na zlepšení zjištěných nedostatků z analytické části.

This bachelor's thesis focuses on evaluating the financial condition of the company JUTA a.s. and on developing proposals for its improvement. The objective will be achieved through a financial analysis covering the period from 2014 to 2023. The thesis is divided into three main parts. The first part presents the theoretical background based on academic literature. In the second part, the theoretical knowledge is applied in the financial analysis of the selected company. The third part is dedicated to proposing improvements for the shortcomings identified in the analytical section.
Evaluation of the Financial Situation of a Company and Proposals for Improvement
Keywords: Finanční analýza; rozvaha; výkaz zisku a ztráty; cash-flow; likvidita; zadluženost; rentabilita; Financial analysis; balance sheet; profit and loss statements; cash-flow; liquidity; indebtedness; profitability